2022
DOI: 10.33899/ijvs.2022.132781.2131
|View full text |Cite
|
Sign up to set email alerts
|

Morphohistopathological alteration in the gills and central nervous system in Cyprinus carpio exposed to lethal concentration of copper sulfate

Abstract: Copper Sulfate (CuSO4) is the most used in aquaculture as chemotherapeutic bath against bacterial, fungal and parasitic diseases but it is very toxic for fish so the goal of this study was to determine the lethal concentration of CuSO4 and evaluate it is toxicity in the gill and central nervous system (brain and spinal cord) in Cyprinus carpio. Fish exposed to 0, 2.5, 5 and 10 mg/L for 24 hours, each concentration with three replication each have six fish. The mortality rate was 100% at concentration 10 mg/L, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…(30). A study reported that the lethal concentrations of CuSO4 at 10 mg/l led to killing the fish, and mortality was 100% during 24 hours, while the concentration at five mg/l was the median lethal concentration which led to killing 50% of treated fish (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…(30). A study reported that the lethal concentrations of CuSO4 at 10 mg/l led to killing the fish, and mortality was 100% during 24 hours, while the concentration at five mg/l was the median lethal concentration which led to killing 50% of treated fish (31,32).…”
Section: Discussionmentioning
confidence: 99%